Influence of different stages of corpus luteum on ovary size, oocytes grades and follicular population in Indian buffaloes - I Osman, Eias Elzein; RK, Sharma.; Badawi, Majdi .E.; S., Dahiya; Y., Prem; A., Pholia; K., Dharmendra; N., Selokar; A., Jerome; K., Pradeep; M., Saini; R., Nidhi; et al. (International Journal of Environment, Agriculture and Biotechnology, 2019)
The aim of this study was to evaluate the effect of different stages of corpus luteum on ovary size, oocytes grades and follicular population. A total of 109 buffalo ovaries were collected from the slaughterhouse and transported to the laboratory for determination of ovaries weight, length, width, thickness, follicular population and oocytes grades. The results obtained revealed that the effect of types of CL on ovary weight and size showed a significant difference in the type of CL groups with ovary weight and ovary size. Ovaries having CL in late-stage showed the highest mean of ovary weight, length, width and thickness over the CL in the early and middle stage. Moreover, the results showed no significantly different in the type of CL groups with follicular population and oocytes grades.